Respiratory syncytial virus disease burden in children and adults from Latin America: a systematic review and meta-analysis - Ciapponi, Agustín; Palermo, María Carolina; Sandoval, María Macarena; Baumeister, Elsa; Ruvinsky, Silvina; Ulloa-Gutierrez, Rolando; Stegelmann, Katharina; Ruesjas, Sofía Ardiles; Cantos, Joaquín; LaRotta, Jorge; de Almeida, Rodrigo Sini; Bardach, Ariel (Frontiers in Public Health, 2024)
Respiratory Syncytial Virus (RSV) is a common cause of lower respiratory tract infections (LRTI) and hospitalization worldwide. The impact of RSV in Latin America and the Caribbean (LAC) including expensive treatment options, such as palivizumab, have been extensively discussed. However, publications on the impact of RSV disease burden in the region are scarce. This systematic review aimed to determine the incidence and prevalence of RSV in LAC by age and RSV subtype.We conducted a systematic review following Cochrane methods to evaluate the disease burden of RSV in LAC countries. We searched studies from January 2012 to January 2023 in literature databases and grey literature without language restrictions. We included guidelines, observational, economic, and surveillance studies from LAC countries. Pairs of reviewers independently selected, and extracted data from included studies. The risk of bias was assessed using the Study Quality Assessment Tools (NHLBI) and AGREE-II. We performed proportion meta-analyses using methods to stabilize the variance. The protocol was registered in PROSPERO (CRD42023393731).We included 156 studies, mainly from Brazil (25%), Colombia (14.5%), and Argentina (13.8%), as well as four clinical practice guidelines. Most studies were cross-sectional (76.9%) and were classified as low risk of bias (52.6%). The majority included inpatients (85.6%), pediatric (73.7%), and normalrisk patients (67.1%). The highest pooled prevalence was estimated in patients <1 year old (58%), with type A and B prevalence of 52% and 34%, respectively. The RSV-LRTI incidence was 15/100 symptomatic infants aged <2 years old, and the ICU admission was 42%. The RSV-LRTI lethality was 0.6%, 3% in patients aged <2 and 0-5 years old, respectively, and 23% among >65 years old high-risk patients. The identified guidelines lack methodological rigor and have limitations in their applicability. The seasonality was more evident in South America than in Central America and The Caribbean, with a clear gap during the pandemic. Conclusions This is the most exhaustive and updated body of evidence describing a significant burden of RSV in LAC, particularly at the extremes of life, and its seasonality patterns. Our findings could contribute could contribute facilitating effective prevention and treatment strategies for this significant public health problem.